Female Labour Force Participation: What Prevents Sustainable Development Goals from Being Realised in Iran? - Elham Taheri (MDPI AG, 2021)
Elimination of the gender gap in labour force participation has become one of the main challenges of achieving the U.N.’s Sustainable Development Goals (SDGs) in the 2030 Agenda for Sustainable Development. The rapid increase in university education and decrease in fertility rate in Iran over the past decades might affect the achievement of the SDGs. However, the country’s female labour force participation (FLFP) rate stagnates at a superficial level. The stagnating FLFP rate is inconsistent with basic labour economics supply-side explanations while drawing attention to demand-side explanations, namely, female labour demand constraints, such as occupational segregation and labour market discrimination. This study empirically investigates the effect on FLFP of primary labour supply factors along with household conditions and gender norms and attitudes for 2 specific years: 2008 and 2018. The aim is to shed light on the causes of stagnation at the FLFP level by using the Household Expenditure and Income Survey conducted annually by the Statistical Center of Iran. The empirical findings suggest gender norms and attitudes towards working women and gendered division of work associated with family care as the driving forces of stagnation in FLFP in Iran.